The feasibility and acceptability of training volunteer mealtime assistants to help older acute hospital inpatients: the Southampton Mealtime Assistance Study. Issue 21 (25th March 2014) - Roberts, Helen C; De Wet, Sanet; Porter, Kirsty; Rood, Gemma; Diaper, Norma; Robison, Judy; Pilgrim, Anna L; Elia, Marinos; Jackson, Alan A; Cooper, Cyrus; Aihie Sayer, Avan; Robinson, Sian
<x xml:space="preserve">Abstract</x> Aims and objectives To determine the feasibility and acceptability of using trained volunteers as mealtime assistants for older hospital inpatients. Background Poor nutrition among hospitalised older patients is common in many countries and associated with poor outcomes. Competing time pressures on nursing staff may make it difficult to prioritise mealtime assistance especially on wards where many patients need help. Design Mixed methods evaluation of the introduction of trained volunteer mealtime assistants on an acute female medicine for older people ward in a teaching hospital in England. Methods A training programme was developed for volunteers who assisted female inpatients aged 70 years and over on weekday lunchtimes. The feasibility of using volunteers was determined by the proportion recruited, trained, and their activity and retention over one year. The acceptability of the training and of the volunteers' role was obtained through interviews and focus groups with 12 volunteers, nine patients and 17 nursing staff. Results Fifty‐nine potential volunteers were identified: 38 attended a training session, of whom 29 delivered mealtime assistance, including feeding, to 3911 (76%) ward patients during the year (mean duration of assistance 5·5 months). The volunteers were positive about the practical aspects of training and ongoing support provided. They were highly valued by patients and ward staff and have continued to volunteer. Conclusions Volunteers can be recruited and trained to help acutely unwell older female inpatients at mealtimes, including feeding. This assistance is sustainable and is valued. Relevance to clinical practice This paper describes a successful method for recruitment, training and retention of volunteer mealtime assistants. It includes a profile of those volunteers who provided the most assistance, details of the training programme and role of the volunteers and could be replicated by nursing staff in other healthcare units.